2016
DOI: 10.1073/pnas.1524861113
|View full text |Cite
|
Sign up to set email alerts
|

An ecocultural model predicts Neanderthal extinction through competition with modern humans

Abstract: Archaeologists argue that the replacement of Neanderthals by modern humans was driven by interspecific competition due to a difference in culture level. To assess the cogency of this argument, we construct and analyze an interspecific cultural competition model based on the Lotka−Volterra model, which is widely used in ecology, but which incorporates the culture level of a species as a variable interacting with population size. We investigate the conditions under which a difference in culture level between cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 46 publications
2
47
0
1
Order By: Relevance
“…Our findings thus fit within more general extensions of mathematical theories of evolution that include formalism from statistical and condensed matter physics [8, 58, 72, 73], suggesting that universal mechanisms may underly subtle transient properties observed in many natural ecosystems, including hysteresis and dynamical robustness [75]. …”
Section: Discussionsupporting
confidence: 68%
“…Our findings thus fit within more general extensions of mathematical theories of evolution that include formalism from statistical and condensed matter physics [8, 58, 72, 73], suggesting that universal mechanisms may underly subtle transient properties observed in many natural ecosystems, including hysteresis and dynamical robustness [75]. …”
Section: Discussionsupporting
confidence: 68%
“…One of the hotly debated topics in human prehistory is the replacement of Neanderthals by modern humans ∼40,000 y ago. A recent study (129) proposed an ecocultural model that incorporated cultural differences between two competing species into Lotka-Volterra competition dynamics and showed that a difference in culture between moderns and Neanderthals could have driven the latter's extinction. This model explicitly includes cultural evolutionary dynamics and shows that a difference in population sizes between moderns in Africa and Neanderthals in Eurasia could have led to a difference in the cultural complexity between the two populations, allowing the small groups of moderns that migrated out of Africa to gradually outcompete the larger population of Neanderthals that they encountered.…”
Section: Models Of Culture and Human Ecologymentioning
confidence: 99%
“…In short, the higher the level of species richness, the greater the number of species likely to evolve, influenced by local and more global conditions, while extinction tended to be more influenced by local ecological factors. These broader studies and the emerging complexity of human evolution point the way to interactions between local and global influences, with variable outcomes, something that can be seen in greater detail in relation to Neanderthal extinction [61,62]. The appearance of new taxa-speciation-and the extinction of existing ones are all significant transitions in human evolution, ones where microevolutionary processes accumulate sufficiently across geographically structured groups for independent lineages to evolve and die out.…”
Section: A Major Transition Is As Much About What Is Missing As What mentioning
confidence: 99%